TEACHER’S STRATEGIES IN TEACHING SLOW LEARNER STUDENTS AT ELEMENTARY SCHOOL - Nur Wahyuni; Zulvia Misykah; Dewi Sartika Panggabean (Jurnal Scientia, 2022)
Teachers realize that each student has different abilities, there are students who can understand the material presented quickly, moderately and slowly. Of course we are very happy if participants can understand the lesson quickly, on the other hand a teacher faces and accepts the situation of students who are indeed slow in learning, based on this problem, this study was conducted aiming to examine strategies that can be applied by classroom teachers in teaching slow students. study. The research method used by the researcher is the literature review method, namely the process of placing, obtaining, reading and evaluating various research literatures related to or related to the problem being studied. The data from this study are the results of research related to the problem of teacher strategies in teaching slow learner students.